Effects of sun exposition on rust and cercospora leaf spot intensity on coffee plants - Augusto de Paiva Custódio, Adriano; Ampélio Pozza, Edson; Augusto de Paiva Custódio, Anselmo; Estevão de Souza, Paulo; Lima, Luiz Antônio; de Lima, Luciana Maria (Coffee Science - ISSN 1984-3909, 2011)
<!--[if gte mso 9]> <![endif]--><!--[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->Knowledge of coffee leaf diseases related to sun exposition can contribute to better sampling techniques to evaluate diseases and reduce agricultural losses. This work evaluated the coffee rust (Hemileia vastatrix Berk. & Broome) and cercospora leaf spot (Cercospora coffeicola Berk. & Cooke (= Mycosphaerella coffeicola (Cooke) Stev. & Wellman)) intensity on coffee leaves (Coffea arabica L.) exposed to North or South. The disease intensity was evaluated at coffee leaves of cultivar Rubi, at average interval of 23 days, from April 2004 to June 2006. The experimental design was randomized blocks at the factorial scheme of 6 water depths x 2 plant sides and 3 replicates, being the plant sides related to North or South direction exposition. The area below the disease progress curve (AACPD) was evaluated and compared through analysis of variance. It was found that the exposition side presented significant differences related to rust occurrence and intensity on both agricultural years 2004/2005 and 2005/2006. Larger increase on rust occurrence was observed on leaves exposed to South compared to North direction. Larger occurrence of shading on plant side turned to South direction and longer leaf wetting periods on this side may have caused the rust progression. For cercospora leaf spot occurrence, significant influence was observed according to plant side only at agricultural year 2004/2005, with larger incidence on those leaves turned to North direction. Larger solar radiation incidence on this side may have been the cause for cercospora leaf spot progress on these leaves. Thus, in order to get more representative leaf samples for rust and cercospora investigation, this study suggests considering plant orientation in relation to sun´s trajectory.